PENEGAKAN HUKUM PEMERINTAHAN TERHADAP AKTIVITAS LESBIAN, GAY, BISEKSUAL, DAN TRANSGENDER (LGBT) DI KOTA PEKANBARU TAHUN 2022-2023 - Dermawan, Muhammad Farhan; ', Isril (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
In this research there is a problem phenomenon raised regarding Government Law Enforcement, there is public unrest regarding the activities of Lesbian, Gay, Bisexual and Transgender (LGBT) people who are proven to have violated Pekanbaru City Regional Regulation Number 13 of 2021 concerning Public Order and Community Peace Article 31 acts that violate norms and decency in public places. So the public demands government law enforcement by the Pekanbaru City Civil Service Police Unit (Satpol PP) and the Government. In efforts to enforce government law against Lesbian, Gay, Bisexual and Transgender (LGBT) activities, the Pekanbaru City Civil Service Police Unit (Satpol PP) adheres to Regional Regulation Number 13 of 2021 concerning Public Order and Community Peace. There are limitations in enforcing this Regional Regulation, namely the absence of a specific chapter regarding Lesbian, Gay, Bisexual and Transgender (LGBT), making Government Law Enforcement limited. Therefore, it is hoped that more optimal control and guidance will have a deterrent effect on perpetrators of these irregularities. This research is descriptive research with a qualitative approach. The types of data used are primary data and secondary data, primary data obtained directly from sources, with secondary data namely supporting data or strengthening primary data. Data collection techniques were carried out by means of interviews and documentation. The results of this research show that Government Law Enforcement and the implementation of Satpol PP's duties in controlling Lesbian, Gay, Bisexual and Transgender (LGBT) activities have been running according to the applicable Standard Operating Procedures (SOP), however there are obstacles by the Pekanbaru City Satpol PP starting from the difficulty identification, as well as perpetrators who fled before being caught in raids, so that the government's role in enforcing existing laws must be stricter with the existence of regional regulations, starting from controlling and sexual development. Keywords: Government Law Enforcement, Pekanbaru City Satpol PP, LGBT